Contribution of the proximal and distal gastric phases to the breakdown of cooked starch-rich solid foods during static in vitro gastric digestion. - Nadia J; Bronlund JE; Singh H; Singh RP; Bornhorst GM (Elsevier, 2022)
In vitro gastric digestion studies commonly focus on the acidic environment of the stomach (the distal phase), neglecting that the contact time between food and salivary amylase can be extended during bolus' temporary storage in the proximal stomach (the proximal phase). Consequently, the role of the proximal phase of gastric digestion on the breakdown of solid starch-based foods is not well understood. This study aimed to address this question using a static in vitro digestion approach. Cooked starch-rich foods of different physical structures (wheat couscous, wheat pasta, rice couscous, rice noodle, and rice grain) were subjected to 30 s oral phase digestion, followed by prolonged incubation of the oral phase mixture (pH 7) for up to 30 min representing different proximal phase digestion times. Each proximal phase sample was sequentially incubated in excess simulated gastric fluid (distal phase, pH 2) for up to an additional 180 min. The proximal phase aided solid food breakdown through starch hydrolysis that caused leaching of particles <2 mm. The distal phase led to softening of food particles, but the softening process was not enhanced with longer proximal phase. In foods with smaller initial size (couscous and rice couscous), a proximal phase of 15 min or longer followed by 180-min distal phase increased starch hydrolysis in the liquid and suspended solid fractions of the digesta, indicating the influence of food structure on acid hydrolysis during in vitro gastric digestion.
Keywords: Acid hydrolysis; Amylolysis; Biochemical breakdown; In vitro gastric digestion; Physical breakdown; Starch; Cooking; Digestion; Edible Grain; Oryza; Starch; Stomach; Triticum